2013
DOI: 10.1155/2013/398194
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Lobectomy Is Associated with Excellent Clinical Outcomes in Properly Selected Differentiated Thyroid Cancer Patients with Primary Tumors Greater Than 1 cm

Abstract: Background and Objective. An individualized risk-based approach to the treatment of thyroid cancer is being extensively discussed in the recent literature. However, controversies about the ideal surgical approach remain an important issue with regard to the impact on prognosis and follow-up strategies. This study was designed to describe clinical outcomes in a cohort of low and intermediate risk thyroid cancer patients treated with thyroid lobectomy. Methods. Retrospective review of 70 patients who underwent l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 15 publications
2
50
1
Order By: Relevance
“…Similar findings were reported by Memorial Sloan Kettering in a matched pair analysis [20]. Single institutions would provide increasingly compelling evidence that more aggressive therapy was not associated with improved outcome [21][22][23][24]. These findings were supported by updated national database studies, which also concluded that a more aggressive approach could not be supported in low-risk groups [25].…”
Section: Prace Poglądowesupporting
confidence: 64%
“…Similar findings were reported by Memorial Sloan Kettering in a matched pair analysis [20]. Single institutions would provide increasingly compelling evidence that more aggressive therapy was not associated with improved outcome [21][22][23][24]. These findings were supported by updated national database studies, which also concluded that a more aggressive approach could not be supported in low-risk groups [25].…”
Section: Prace Poglądowesupporting
confidence: 64%
“…The major reasons included the following: low complication rate associated with TT (as reported by several authors) [27][28][29], risk of relapse after hemithyroidectomy [5,7], risk of an occult malignancy [30] that makes follow-up complex, and/or greater difficulty in performing the revision surgery after thyroid lobectomy. Several recent studies have emphasized various advantages of hemithyroidectomy [31,32] in selected cases of malignancy [33,34]. Further observations may reinforce the support of HT such as voice and swallowing disorders that have been evaluated in association with TT [35,36].…”
Section: Discussionmentioning
confidence: 88%
“…Traditionally, the initial treatment of PTC has included a total thyroidectomy, often with radioactive iodine remnant ablation (2). However, a more risk adapted management approach has been followed at many centers (3,4) and is now being endorsed in both the National Comprehensive Cancer Center and the American Thyroid Association guidelines (5,6).…”
mentioning
confidence: 99%